2015
DOI: 10.1016/j.jvs.2015.06.102
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Outcomes of Civilian Lower Extremity Arterial Trauma

Abstract: and the prevalence of PAD in individuals who underwent vascular screening and BMD measurements.Methods: Patients underwent arterial Doppler studies; PAD was noted with an ankle-brachial index of #0.9. T scores were calculated using bone densitometry of the calcaneus. Normal was a T score of À1.0 or higher, osteopenia with a T score between À1.0 and À2.5, and osteoporosis with a T score of À2.5 or lower. Subject demographics, comorbidities, and history were self-reported. Univariate and multivariate statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 7 publications
0
16
0
2
Order By: Relevance
“…The incidence of lower extremity arterial injury has been reported to occur in approximately 0.3% of all civilian trauma admissions. 2 Arterial injuries resulting from blunt trauma are even more rare and require a high-impact mechanism. 4 A study of 651 infra-inguinal arterial injuries identified from the NTDB found that 34% (n = 220) of injuries resulted from blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of lower extremity arterial injury has been reported to occur in approximately 0.3% of all civilian trauma admissions. 2 Arterial injuries resulting from blunt trauma are even more rare and require a high-impact mechanism. 4 A study of 651 infra-inguinal arterial injuries identified from the NTDB found that 34% (n = 220) of injuries resulted from blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…1 Femoral vessel injuries in particular account for the majority of lower extremity vascular injuries (LEVI), most commonly the consequence of penetrating mechanisms. 1,2 Blunt arterial injuries develop from the stretch or shearing force but can also culminate from a contusion or crushed extremity. Historically, LEVIs had substandard survivability; however, surgical management has evolved leading to lower mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of arterial injury after blunt lower extremity fractures has been reported as 1.04%. 2,3 Popliteal artery injury associated with a tibial plateau fracture with PCL avulsion fracture is a rare condition. Therefore, close monitoring of this condition is required.…”
Section: Introductionmentioning
confidence: 99%
“…Se compromete en mayor medida las extremidades inferiores 31-36%, seguido de las extremidades superiores 18,4-31%, vasos abdominales y pélvicos 15,6-21%, cuello 10-24,8% y tórax 10-13,8% 3,6,7 . La severidad y el mecanismo de las lesiones han sido descritos en relación a la necesidad de manejo quirúrgico que varía entre 2-60% de todas las lesiones vasculares 1,2 . Dentro de los procedimientos requeridos en la reparación de estas lesiones se encuentran las ligaduras vasculares, reparos primarios, bypass o la embolización selectiva; tales procedimientos presentan complicaciones postquirúrgicas como la trombosis o estenosis del reparo en un 3%, infección del sitio operatorio, reintervención por alguna causa relacionada al procedimiento inicial de 7,7% y las amputaciones 3,3-29% 8,9 .…”
Section: Introductionunclassified
“…Dentro de los procedimientos requeridos en la reparación de estas lesiones se encuentran las ligaduras vasculares, reparos primarios, bypass o la embolización selectiva; tales procedimientos presentan complicaciones postquirúrgicas como la trombosis o estenosis del reparo en un 3%, infección del sitio operatorio, reintervención por alguna causa relacionada al procedimiento inicial de 7,7% y las amputaciones 3,3-29% 8,9 . La mortalidad relacionada a estas lesiones se ha descrito alrededor del 2-22,9% 6,7,9 estos valores varían dependiendo de las variables como la energía del mecanismo de la lesión, tiempo de evolución a la atención, el sitio de la lesión, lesiones asociadas, tipo de reparo y características operativas de la cirugía inicial, entre otras 2,11 .…”
Section: Introductionunclassified